Sport, Disability and Social Integration - Fizzotti, Gabriella; Tsampas, Nikolas; Vigorelli, Vanessa (British Journal of Healthcare and Medical Research, 2024)
Introduction: One of the most relevant disabilities is caused by Spinal Cord Injury (SCI). Typical causes of spinal cord damage are trauma, disease, or congenital disorders. In most cases SCI leads to paraplegia or quadriplegia. Sports activities are implemented during and after the rehabilitation of SCI people in order to improve strength, aerobic fitness, and physical functioning; in addition, sports activities have positive effects on psychological well-being. The purpose of this qualitative study was to evaluate the contribution of sporting activity to the individual rehabilitation project and to compare the personal experiences of professional agonist athletes. Material and Methods: A total of twenty-one individuals: twelve males, nine females were recruited currently participating in wheelchair handbike (11), wheelchair archery (2),wheelchair tennis (1), wheelchair ski (1), canoe (1), bicycle (5) were recruited. Their ages ranged between 23 and 56. A handcycle is a type of vehicle powered by the arms rather than the legs, as on a bicycle. An informational interview is planned with the goal of gaining specific information and making better comparison. Questions concern: individual medical history, rehabilitation program, sport and athletic individual results, final considerations. Results: In eleven handbikers it has been possible confirmed the tangible increase in muscle strength of the upper limbs, the main motor of propulsion in hand bikes. From the psychological point of view to begin this new sport has given them a concrete goal to follow. This new activity has allowed them to constantly improve and to meet new people who share them own difficulties and mostly the same passion. Conclusions: The contribution of sport in rehabilitation program is important because it can be used as a tool to improve the body’s compromised motor functions. Emerging evidence indicates that exercise and sports can have significant physical and psychosocial health benefits for people with SCI.